2015
DOI: 10.1159/000444366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Host and Viral Factors on Patients with Chronic Hepatitis C Virus Genotype 6 Treated with Pegylated Interferon and Ribavirin: A Systematic Review and Meta-Analysis

Abstract: Objectives: We conducted a systematic review and meta-analysis of the influence of host and viral factors on the sustained virologic response (SVR) in hepatitis C virus genotype 6 (HCV-6) patients treated with pegylated interferon (PEG-IFN) and ribavirin (RBV). Methods: Data were retrieved fromMedline, Embase, PubMed and the Cochrane Library for ‘genotype 6' studies published up to December 2014 and for abstracts from international scientific meetings. Inclusion criteria were efficacy of PEG-IFN+RBV based on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…In this study, the SVR rate of patients using the traditional interferon treatment was only 65.2%, which was slightly lower than that of relevant studies and related statistics at within China and abroad ( 1 , 21 ): the SVR rate of patients using the DAA drug treatment was 97.4%, which was basically consistent with the statistics of other relevant real-world clinical studies and guidelines ( 6 , 22 ), further verifying the effectiveness of DAA drugs. Among the patients who were cured, the average treatment time of patients using DAA drugs was 2.65 months, which was only one-sixth of the traditional interferon treatment time.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the SVR rate of patients using the traditional interferon treatment was only 65.2%, which was slightly lower than that of relevant studies and related statistics at within China and abroad ( 1 , 21 ): the SVR rate of patients using the DAA drug treatment was 97.4%, which was basically consistent with the statistics of other relevant real-world clinical studies and guidelines ( 6 , 22 ), further verifying the effectiveness of DAA drugs. Among the patients who were cured, the average treatment time of patients using DAA drugs was 2.65 months, which was only one-sixth of the traditional interferon treatment time.…”
Section: Discussionsupporting
confidence: 85%
“…Different direct-acting antiviral (DAA) therapies appeared to have various sustained virologic response (SVR) for different HCV genotypes. A systematic review and meta-analysis revealed that SVR of the PEG-IFN+RBV regimen to HCV genotype 6 was similar to genotypes 2 and 3, but higher than genotype 1 (Thong et al, 2015). The safety and efficacy of SOF-based DAA regimens for treatment of HCV genotype 6 were well demonstrated by some studies conducted in China and the United States (Wong et al, 2017; Hu et al, 2018; Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…33 Consistent with the present results, the authors of that meta-analysis showed that IFNL4 rs368234815 can predict SVR in HCV patients, which is independent of HCV genotype, patient ethnicity, and treatment regimen. A considerable number of studies have focused on this, 34,35 and the role of IFNL4 becomes more and more evident.…”
Section: Discussionmentioning
confidence: 99%